(untitled) (International Journal of Engineering and Computer Science, 2025)
Artificial Intelligence (AI) is revolutionizing healthcare by enhancing diagnostic precision, optimizing treatment plans, and streamlining operational workflows. This survey paper explores the current landscape of AI applications in healthcare, focusing on technologies such as machine learning, deep learning, natural language processing, and computer vision. We review their roles in disease detection, drug discovery, patient monitoring, and data security, drawing insights from recent studies. While AI offers significant benefits, including improved patient outcomes and cost efficiency, challenges such as data privacy, ethical concerns, and algorithmic bias persist. This paper synthesizes findings from diverse research efforts, identifies trends, and proposes directions for future investigation to ensure responsible AI integration in healthcare.